Estandarización del proceso de producción de balanceado en la Empresa Grupo Avícola San Vicente de Riobamba - Pazmiño Orozco, Diego Fernando (2021)
The groupal Avícola San Vicente company located in the city of Riobamba is an organization dedicated to the production of fattening food, chicken grow up, slaughter and sale of slaughtered chickens. The present research aims to standardize the production process in the elaboration of fattening food for chicken powder type with the purpose of controlling its internal processes regarding the production of fattening food for chicken powder type, collecting and documenting the information in order to minimize existing errors. For the present investigation, it was analyzed by direct observation, the respective times were taken in each process, the standard time was determined using the Westinghouse method, a manual of instructive procedures and records for production line fattening food for chicken powder type, to serve as a guide for the different operations to be carried out. With the standard time found, a proposal was made to improve the time, thus obtaining a standard time of 99.46 min (2h: 5 min) and with the proposed method we had a time of 98.21min (2h: 3 min) per batch of production obtaining time saved by eliminating a bottleneck of 2 min per production batch